Passive Investoren Indexbasierte Vermögensverwaltung und die Corporate Governance der Publikumsgesellschaft - Steuer, Sebastian (Gesamtes Recht der Unternehmen und Finanzen, 2022)
The rise of index funds presents a challenge for the corporate governance of listed companies. Based on a comprehensive data analysis, the thesis documents the growing importance of passive asset managers in listed firms' ownership structures. It then explains why the incentives of these managers to engage in the corporate governance of their portfolio companies are not socially optimal, relying, among other things, on recent results from the empirical corporate finance literature. Finally, the thesis critically reviews the instruments employed by the legal system to respond to the problems identified, with a focus on the "stewardship" provisions of the revised Shareholder Rights Directive and the shortcomings of their specific design.